Rhytidhysteron mangrovei (Hysteriaceae), a new species from mangroves in Phetchaburi Province, Thailand - Kumar, Vinit; Cheewangkoon, Ratchadawan; Thambugala, Kasun M.; Jones, Gareth E.b.; Brahmanage, Rashika S.; Doilom, Mingkwan; Jeewon, Rajesh; Hyde, Kevin D. (Phytotaxa, 2019)
During an investigation of micro-fungi inhabiting mangrove forests, a new species of Rhytidhysteron was collected and isolated from dead twigs of a mangrove tree. Rhytidhysteron mangrovei sp. nov. is introduced, described, illustrated and compared with accepted species in the genus. Morphological comparison based on the size of exciple, the appearance of ascomata and ascospore septations and size as well as the multi-gene phylogenetic analyses based on LSU, ITS and TEF DNA sequences support its establishment in Rhytidhysteron. Placement of the genus in Hysteriaceae is also well-supported. In addition, phylogenetic analysis and DNA sequence data indicate that Rhytidhysteron mangrovei is closely related to Rhytidhysteron thailandicum. However, R. mangrovei is morphologically distinct from R. thailandicum, by having a relatively smaller size of exciple and perpendicularly rough-striate ascomata.